The Success of Learning Organisation: Values Contextualization Dimension - Biruta Švagždienė; Edmundas Jasinskas; Artūras Simanavičius (Montenegrin Journal of Economics)
Achievement of competitive advantages in the organization are a key driver for business success in companies. However, if these factors do not become an integral part of the organization's identity, it is not possible to achieve a competitive advantage. The goal of the article is to investigate the developed values of learning organization and to determine their relationship dependence on environmental factors through a perception of healthy lifestyle as a value. Methods used for scientific research – scientific literature analysis, structured interview. The hypothesis of the research – Do the educational factors influence the formation of values in modern organizations? Conclusions. The main cause which determine gap between organizations declared publicly values and its application in practice is disharmony between organization's values and fundamental moral society values. Social responsibility in this case has not become an integral part of the organization's values yet. Education values is an integral part of each learning organization that promotes human development. Health education is an integral part of health promotion activities, including psychosocial and physical aspects and should be seen in the overall context of the entire education system.